Watershed Flood Control Performance and Possibilities - Frank, Bernard; Munns, E. N. (Indian Forester, 1946)
Foresters and other conservationists have been acquainted only to a limited extent with the watershed phase of the national flood control program. The results of five years activity in this field now permit a thorough appraisal of performance and possibilities. Detailed analyses of the program and especially the completed survey reports reveal desirable and undesirable features involving both principles and procedures, Because of the sharp significance of flood and sedimentation damage and the increasing responsibility of land users and managers in its alleviation, results of the watershed investigations and operations here described are of considerable practical interest.